Time-Domain Extreme-Ultraviolet Diffuse Scattering Spectroscopy of Nanoscale Surface Phonons - Capotondi, F.; Maznev, A. A.; Bencivenga, F.; Bonetti, S.; Engel, D.; Fainozzi, D.; Fausti, D.; Foglia, L.; Gutt, C.; Jaouen, N.; Ksenzov, D.; Masciovecchio, C.; et al. (Physical Review Letters, 2025)
We report the observation of dynamic fringe patterns in the diffuse scattering of extreme ultraviolet light from surfaces, following femtosecond optical excitation. At each point on the detector, the diffuse scattering intensity exhibits oscillations at well-defined frequencies that correspond to surface phonons with wave vectors determined by the scattering geometry, indicating that the optical excitation generates coherent surface phonons propagating in all directions and spanning a wavelength range from 60 to 300 nm. This phenomenon is observed on a variety of samples, including single-layer and multilayer metal films, as well as bulk semiconductors. The measured surface phonon dispersions show good agreement with theoretical calculations. By comparing signal amplitudes from samples with different surface morphologies, we find that the excitation mechanism is linked to the natural surface roughness of the samples. However, the signal is still detectable on extremely smooth surfaces with subnanometer roughness. Our findings demonstrate a simple and effective method for optically exciting coherent surface phonons with nanoscale wavelengths on a wide range of solid samples and establish a foundation for surface phonon spectroscopy in a wave vector range well beyond the limit of conventional surface Brillouin scattering.
CRIS-Team Scopus Importer:2026-01-26